Aircraft maintenance enterprises expenditures formation economic model: Solution problems and directions - Podolyakina, Natalia (Transport, 2005)
Under contemporary economic conditions the businessman is interested in the optimization of expenses. Equipment maintenance is one of the components of the enterprise expenses. That is why it is necessary to develop the model of the formation of the enterprise expenses aimed to the technical equipment maintenance. This model is taken into serious consideration making serious and thorough decisions on the quantity of expenses for providing the appropriate working equipment state and reliability level. First Published Online: 27 Oct 2010